Triploid Induction in the Yellowtail Tetra, Astyanax altiparanae, Using Temperature Shock: Tools for Conservation and Aquaculture - Macedo Adamov, Nadya Soares de; Nascimento, Nivaldo Ferreira do [UNESP]; Silva Maciel, Elayna Cristina; Pereira-Santos, Matheus [UNESP]; Senhorini, Jose Augusto; Calado, Leonardo Luiz; Evangelista, Mariana Machado [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Marin Guerrero, Alan Hertz; Fujimoto, Takafumi; Yasui, George Shigueki (Wiley-Blackwell, 2017)
Triploidization is an interesting tool to produce sterile fish. In the yellowtail tetra, Astyanax altiparanae, this can be applied for aquaculture and surrogate technologies. In this study, we compared the efficacy of cold (2 C) or heat shock (38 C, 40 C, and 42 C) on triploid induction in the yellowtail tetra. The eggs were treated with cold or heat shock, 2 min postfertilization (30min in cold shock or 2min in heat shock). Intact embryos served as the control group. Ploidy status was confirmed by karyotyping, flow cytometry, and nuclear diameter of erythrocytes. The hatching rate decreased after cold shock (12.69 +/- 15.76%) and heat shock at 42 C(0.35 +/- 0.69%) in comparison with the control group (63.19 +/- 16.82%). At 38 C and 40 C, hatching rates (61.29 +/- 17.73% and 61.75 +/- 22.1%, respectively) were not decreased. Only one triploid arose at 38 C (1/80). At 40 C, a high number of triploids arose (72/78). At 42 C, very few embryos developed into the hatching stage. A large number of haploid individuals arose after cold shock (61/75), with only one triploid. Our results indicate that heat shocking of embryos at 40 C is optimum for triploid production in the yellowtail tetra.